Os 3P's da produção cultural: Brasil de Tuhu da concepção do projeto à promoção de uma experiência cultural - Costa, Fabiana de Oliveira Martins da (2012)
This research regards the experience of performing a cultural project, based on the analysis of the Cultural Production 3 Ps. The paper presents an account of the backstages, since the project planning up to its evaluation, bringing a critical reflection on the making of the cultural production and exploring issues related to access and cultural citizenship. The project analyzed here was sponsored through the Brazilian Federal Law of Cultural Incentive (Rouanet Law). The dynamic game of the cultural market here exposed presents a form of interaction between the Proponent, the Project Sponsor and the Public that serves as reference to comprehend the trajectory of a cultural project since its creation, going through its implementation and up to its finalization. Another aspect here explored, although yet less developed in the market, treats about the establishment of the bases for the evaluation of the social-cultural projects results achieved.